Carbon dioxide, ground air and carbon cycling in Gibraltar karst. (1st July 2016) - Mattey, D.P.; Atkinson, T.C.; Barker, J.A.; Fisher, R.; Latin, J.-P.; Durrell, R.; Ainsworth, M.
Highlights: A new generic model of carbon cycling in the vadose zone of karst systems. Mathematical and chemical models that explain ventilation, p CO2 and carbon isotope ratios in ground air. Most vadose CO2 is generated from organic matter transported downwards into the vadose zone. The standard model is a special case of the generic 'Gibraltar model'. Abstract: We put forward a general conceptual model of CO2 behaviour in the vadose zone of karst aquifers, based on physical principles of air flow through porous media and caves, combined with a geochemical interpretation of cave monitoring data. This 'Gibraltar model' links fluxes of water, air and carbon through the soil with the porosity of the vadose zone, the circulation of ground air and the ventilation of caves. Gibraltar hosts many natural caves whose locations span the full length and vertical range of the Rock. We report results of an 8-year monitoring study of carbon in soil organic matter and bedrock carbonate, dissolved inorganic carbon in vadose waters, and gaseous CO2 in soil, cave and ground air. Results show that the regime of cave air CO2 results from the interaction of cave ventilation with a reservoir of CO2 -enriched ground air held within the smaller voids of the bedrock. The p CO2 of ground air, and of vadose waters that have been in close contact with it, are determined by multiple factors that include recharge patterns, vegetation productivity and root respiration, and conversion of organic matter to CO2 within the soil, the epikarst and the whole vadose zone. Mathematical modelling and field observations show that ground air is subject to a density-driven circulation that reverses seasonally, as the difference between surface and underground temperatures reverses in sign. The Gibraltar model suggests that cave air p CO2 is not directly related to CO2 generated in the soil or the epikarstic zone, as is often assumed. Ground air CO2 formed by the decay of organic matter (OM) washed down into the deeper unsaturated zone is an important additional source of p CO2 . In Gibraltar the addition of OM-derived CO2 is the dominant control on the p CO2 of ground air and the Ca-hardness of waters within the deep vadose zone. The seasonal regime of CO2 in cave air depends on the position of a cave in relation to the density-driven ground air circulation pattern which is itself determined by the topography, as well as by the high-permeability conduits for air movement provided by caves themselves. In the steep topography of Gibraltar, caves in the lower part of the Rock act as outflow conduits for descending ground air in summer, and so have higher p CO2 in that season. Caves in the upper Rock have high p CO2 in winter, when they act as outflow conduits for rising currents of CO2 -enriched ground air. Understanding seasonal flows of ground air in the vadose zone, together with the origins and seasonal regimes of CO2 in cave air underpins robust interpretation of speleothem-based climate proxy records.